Penerapan Metode Six Sigma untuk Menurunkan Jumlah Defect pada Produksi Fillet Ikan Kakap Putih (Lates Calcarifer Bloch) - Putu Ayu Aripradnyani; I Wayan Widia; I Gusti Ketut Arya Arthawan (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
Every company should try to minimize the risk of failure in production. The high percentage of defective products in each production cycle has implications not only reducing consumer confidence but also increasing production costs, which results in lower product competitiveness in the market. The objective of this study was to identify the main factors causing defects in the product and to find how can of process improvement and or management that can be done to reduce the number of defective products in the export quality white snapper fillet production process at a fish processing company in Bali using the Six-Sigma method. This research consisted of Six-Sigma implementation stages, namely DMAI (Define, Measure, Analyze, and Improve) which involved management and company employees. The results showed that two critical factors were identified as the main causes of white snapper fillet defect, namely broken/mushy and smelly meat, and uneven application of CO gas. The performance characteristics achieved by the company are currently characterized by a DPU (Defect per Unit) number of 0.09, DPO (Defect per Opportunities) of 0.045, DPMO (Defect per Million Opportunities) of 45.463 which is equivalent to performance at the 3,125- Sigma level so that belongs to the category of industry average performance level. The company has the potential to achieve an increase in performance up to the 4,000-Sigma level as long as it is willing to make a number of continuous improvements in handling both the quality control of fish raw materials and imperfections in the supply of CO gas in the product. With application of the six sigma method, the main causes of failure can be identified and get recommendations for improvements in an effort to improve the company’s process performance.